(untitled) ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2017)
Background: Hospitality industry, it all depends on the people, and people working in the hospitality industry need to be different and have specified characteristics. Retention of the key employees is critical to long term health and success of any organization. Objective: To examine the effect of salary structure; wage administration; training and if CSR has impact on employee retention in hotel industry. Methodology: 103 employees of Hotel Dolphin, Digha were the subjects for the study. These subjects were given a structured questionnaire to collect data on employee retention parameters. Results: Salary, wage administration, training, CSR has positive influence on job satisfaction and consequently job satisfaction influences the employee retention. Conclusion: Improvement in the satisfaction level of employees is needed in terms of present benefits, present compensation, work life balance, relation with superior/manager as an individual, training to improve job performances, cooperation from management in terms of operation, relation between employees and other employees, understanding of business strategy at the lower employee level and offer membership program